A függetlenség mint hübrisz (Az ember és a természet kölcsönhatása az Alföldön) - Horváth, Benő (Tér és Társadalom, 1993)
Following the regulation of the rivers, the greatest loss was the elimination of the dialogue between settlement and environment. Traditions lost their meanings due to the fundamental change of the environment, and so did rituals, and the century-old social behaviour built on them, and the lifestyles controlling the everyday life of the settlement. The formation of new settlements and the indirect, and increasingly intensive relations between the settlements pulled the smaller communes into the catchment area of a bigger centre (Fig. 2). New needs increased the agricultural production of the settlements. These needs were are not those of the local community anymore. They are however, several times bigger than them, so the production stimulated by them has no dialogue with the environment. The feedback mechanism that had meant a continuous control, was over, so the lifestyles built on them lost their meanings, too. Szabó, P. was right when writing half a century ago that by the regulation of the rivers "...the world of Hungarian Atlantis disappeared for ever..." (Szabó, P.). The fact that organisations of nature- and environmental protection were set up in order to compensate for the situation is of no help. This is because the dialogue will take place here, in the fields. The village will go on having the responsibility of buffering, the decreasing of opposites, the maintenance of the dialogue between nature and urban environment. With growth of independence this role disappeared – the village became urbanised. Its independence is a seeming one, however, since it still lives on its environment. Sooner or later we have to pay the price of this Hybris. The consequence is the situation our environment shows us. We can't help but admit that the experience of thousands of years, the analysis of ancient civilisations built by myths and rituals deserve more attention. It is not that we should restore this ancient system, but how to take up the dialogue again here and now, using the ancient experiences, by creating the foundations of a new social, technological and moral system, that could serve as the basis of the sustainable development. We should realise (and our ancestors were very much aware of it), that the strategy of the long-term survival of a civilisation is based on ethical grounds. From this point of view the situation of our country is extremely lucky. There is something in the formation of the world of scattered farms, this typical Great Plain feature, that, besides the re-formation of the space, lets us see the rudiments of the willingness for this ancient dialogue. No where else in Europe has there ever been such a lasting and harmonic co-existence with Nature as here in Hungary. So the study of its rituals, traditions, and the social structure built on them can be of a great importance for the restoration of the social order of the Great Plain's small settlements, that have lost direction, continuity and an inner value system. With the exception of economic actors, it is evident now for all social layers that the maintenance of the present lifestyle of our civilisation is a self-destroying process.